Pengaruh Pemberdayaan Masyarakat Terhadap Pencegahan Monkeypox (MPOX) di Sekitar Taman Rekreasi Wendit Pakis Kabupaten Malang - Defia Dea Amanda; Sugianto Hadi; Sri Winarni; Farida Halis (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Monkeypox (MPOX) is a zoonotic infection transmitted through direct contact between humans and animals. Although no confirmed cases have been reported in Malang Regency, Wendit Recreational Park (TRW) has a high potential for transmission due to human interaction with wild monkeys. This study aimed to determine the effect of community empowerment on preventive behavior (knowledge, attitudes, and practices) toward MPOX in the TRW area. This study used a quasi-experimental design with a pre-test and post-test control group. A total of 60 respondents were selected using stratified random sampling and divided into intervention and control groups. Community empowerment was conducted through handwashing with soap (CTPS) demonstrations and educational flyers. Data were collected using questionnaires and CTPS observation sheets. Following the community empowerment intervention, significant improvements were observed in knowledge (p=0.000), attitudes (p=0.000), and preventive practices (p=0.000) regarding MPOX in both the intervention and control groups. These results contributed to the commitment of the TRW community to engage in MPOX prevention efforts, including the consistent application of the six-step handwashing with soap (CTPS) method. Community empowerment significantly influences MPOX prevention behavior around Wendit Recreational Park, Pakis, Malang Regency.